The Efficiency of Solar Panels and Power Control - Sabzalian , M (Elsevier, 2024)
Solar panels are a good alternative to fossil fuels. However, despite their numerous advantages, their most important limitation is dependence on environmental conditions. To solve this problem, energy storage systems are used with solar panels. To set a fixed output voltage requires designing a strong switching system to use stored energy when solar energy drops below the required value due to environmental conditions, and to store it in a storage system when there is a surplus of solar energy. Moreover, solar panels have different capacities in different currents and always produce the most power in a specific current. This chapter investigates one of the effective controllers. Also solar panel modeling methods are reviewed. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.
Keywords: energy control; fuzzy control; Solar panel; switching system; type-2 fuzzy system